Towards a dynamic discovery of smart services in the social internet of things. (February 2017) - Hussein, Dina; Han, Son N.; Lee, Gyu Myoung; Crespi, Noel; Bertin, Emmanuel
Highlights: Social Internet of Things (SIoT) extends the paradigm of IoT with its improved intelligence, user friendliness and context-awareness. The intelligence needed to integrate objects, services and people as the core of SIoT paradigm, increases the quantity and the variety of contextual data that must be handled. Two kinds of contextual data exist typically in SIoT scenarios; objective and subjective context; combining objective and subjective context for intelligent decision making is necessary for achieving situation-awareness (SA) in smart environments. Abstract: The paradigm of the Social Internet of Things (SIoT) boosts a new trend wherein the connectivity and user friendliness benefits of Social Network Services (SNS) are exhibited within the network of connected objects, i.e. the Internet of Things (IoT). The SIoT exceeds the more traditional paradigm of IoT with an enhanced intelligence and context-awareness. In this paper, a novel service framework based on a cognitive reasoning approach for dynamic SIoT services discovery in smart spaces is proposed. That is, reasoning about users' situational needs, preferences, and other social aspects along with users' surrounding environment is proposed for generating a list of situation-aware services which matches users' needs. This reasoning approach is then implemented as a proof-of-concept prototype, namely Airport Dynamic Social, within a smart airport. Finally, an empirical study to evaluate the reasoning approach's efficiency shows improved services adaptability to situational needs compared to common approaches proposed in literature. Graphical abstract: